L2 teachers' knowledge of L2 learners’ listening and oral interpretation problems: Any correspondence? - Karim Sadeghi; Mohammad Ali Rahimi (Edukasi, 2019)
The study was aimed at comparing learners’ knowledge of their listening and oral interpretation problems with their teachers’ perception and knowledge of the same problems. Fifty two learners in company with their three instructors participated in the study. The study tapped the students’ reflections on cognitive, affective and linguistic factors impinging on listening and oral interpretation processes and teachers’ perception and knowledge of the same real time listening and interpretation tasks. Introspection techniques, observation and interviews were the main techniques of data collection. Data analysis revealed many congruencies between the learners and their instructors in terms of the listening experiences and perceptions. They included such themes as ‘ineffective strategy of focusing on words’, ‘speedy delivery’, ‘difficulty level of the material’, ‘accent effect’ and ‘parsing problem’. However, some discrepancies were also identified with regard to such core themes as ‘modality’ and affective issues such as ‘stress’, ‘sense of fatigue’ and ‘concentration loss’. The results suggest that instructors’ perception and awareness of their learners’ listening processing and oral translation skills coupled with those of learners can provide rich information in developing listening and oral interpretation programs for translation students and trainers. Key words: oral interpretation, listening processing, knowledge, perception